Teaching the Past Form to the Students of SMAN 5 Palu through Group Work Learning - Yohalis Selma Sunggudek; Wahyudin Wahyudin; Desrin Lebagi; Rofiqoh Rofiqoh (Journal of English Language and Education, 2026)
Grammar mastery, particularly in the use of past forms, is essential for developing students’ writing skills. However, many students still experience difficulties in applying regular and irregular verbs correctly. This study aimed to examine the effectiveness of group work in improving students’ mastery of past forms. The research employed a quantitative approach with a quasi-experimental design involving an experimental class and a control class, each consisting of 23 tenth-grade students of SMAN 5 Palu. Data were collected through pre-tests and post-tests consisting of multiple-choice and essay questions. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s Test of Homogeneity, and the Mann–Whitney U Test with the assistance of IBM SPSS Statistics version 29. The pre-test results showed that both groups had relatively similar initial abilities, with mean scores of 78.91 for the experimental class and 80.21 for the control class. After six meetings of treatment using group work activities, the experimental class achieved a higher post-test mean score (87.39) than the control class (81.19). The Mann–Whitney U Test showed a significance value of 0.000 (Asymp. Sig. 2-tailed 0.05), indicating a statistically significant difference between the two groups. These findings reveal that students taught through group work performed better in understanding and using regular and irregular verbs. Therefore, group work is effective in improving tenth-grade students’ mastery of past forms in writing at SMAN 5 Palu